Influence of support group intervention on quality of life of Malaysian breast cancer survivors - Abu Kassim , Noor Lide; Mohd Hanafiah, Khayriyyah; Samad Cheung, Humairah; Rahman, Mohammad Tariqur (Sage Publications, Inc., 2013)
Given that breast cancer is the most prevalent form of cancer affecting Malaysian women and its low survival rate, this study investigates the possible influence of support group intervention on quality of life (QOL). It also examines the interrelationships between QOL subdomains as research has shown the influence of emotional expression on psychological and physical wellbeing. Rasch analysis was implemented to examine perception of QOL and the comparability of the Functional Assessment of Cancer Therapy General and Breast Cancer scales (FACT-G and FACT-B) of the Functional Assessment of Chronic Illness Therapy inventory. Results indicated that perception of QOL may be influenced by factors other than support group intervention. The FACT-G and FACT-B scales were comparable in the measurement of QOL for breast cancer, and the interrelationships between the QOL subdomains were supported. The findings of this study accentuate the importance of focusing support group interventions on improvement of emotional well-being to maintain patients’ QOL despite the cancer.